Electrical studies of annealing effect in BST thin film with different doping concentration of indium (III) oxide - Nurjuliana, Juhari; Norzahiyah, Nordin; Noraini, Othman (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Organized by Institute of Electrical and Electronics Engineers (IEEE) in collaboration with Electron Device Society (EDS) and Universiti Kebangsaan Malaysia (UKM), 10th - 12th August 2009 at Renaissance Hotel, Kota Bahru, Kelantan, Malaysia,